First Language Use in the Context of Iranian EFL Classroom Discourse / Amirabbas Ghorbani - Ghorbani, Amirabbas (2013)
As English language education has received prominent attention in non-English-speaking countries, the use of learners‘ first language (L1) becomes a pervasive reality in the classroom. The literature on the use of L1in L2 classroom shows that it has become a long-standing controversy in the field. This research examines the use of L1 in EFL classroom discourse in the Iranian socio-educational context. The study theoretically situates itself at the juncture of interaction analysis and ecological perspective. Over thirty six hours of classroom talk in two language institutes and two high schools were audio taped, videotaped and transcribed. Classroom interactions were observed and coded in COLT A in real time. The episodes of L1 use in classroom interactions were extracted and coded in COLT B. The classroom teachers and institute managers were also interviewed. A questionnaire was used and focus group discussions were conducted to collect learners‘ views towards the use of L1. Six major areas in which L1 appeared were speaking, grammar, listening, vocabulary, homework and off task. The detailed analysis of the areas and the activities revealed that the students used L1 in speaking area activities more than the teacher and the teacher‘s use of L1 was mainly in grammar area activities especially in grammar presentation. Students‘ views were categorized in terms of L1 use for medium-oriented goals with focus on the teaching of the medium or the target language, and framework-oriented goals, which are related to the organization and management of classroom activities. The perceived dangers of the use of L1 and the affective role of L1 use were also reported from the learners‘ view point. Teachers‘ beliefs on the cognitive-driven use of L1, context-driven use of L1, the affective role of L1, and their theories towards the use of L1 in the classroom emerged from the data. The interviews with managers revealed their attitudes toward the use of L1 in the classroom. Apart from the interactional features of L1 use in EFL classroom discourse, the findings of this study provide a holistic image of the effects of different educational settings within the Iranian socio-educational context. Specifically, the findings suggest a more dynamic approach through the consideration of the impact of mainstream educational practices and socio-educational factors on learners‘ views and practices towards the use of L1. The study contributes to a relatively new line of research into L1 use in EFL settings, and to the extensive body of research into classroom discourse.